THE VOCABULARY OF SUBJECT-SPECIFIC TERMINOLOGIES: PECULIARITIES OF COMPOSITION AND FORMATION (BASED ON THE ENGLISH GEODETIC TERMINOLOGY) - Hrybinyk, Yuliia; Sunko, Nataliia (My University, 2023)
The article is dedicated to the study of English geodetic terminology. This paper aims to investigate the vocabulary of the researched terminology, to define the main mechanisms of geodetic terms creation and analyse their productivity. The carried-out investigation allows to draw the following conclusions: 1) English geodetic terminology covers such types of vocabulary: general language words, general scientific and trans-disciplinary terms, subject-specific (geodetic) words; 2) the analysed terminological units are formed on the basis of the following mechanisms: morphological means; semantic means; syntactic method and borrowing; 3) the most productive ones are the creation of terminological word combination and affixation.
Keywords: terminology, geodetic terms, term formation